2014
DOI: 10.2460/ajvr.75.9.792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tibial plateau angle and spacer thickness applied during in vitro canine total knee replacement on three-dimensional kinematics and collateral ligament strain

Abstract: Among the constructs tested, greatest normalization of canine stifle joint kinematics in vitro was achieved with the steepest plateau angle paired with the thinnest spacer. Furthermore, results indicated that strain to the collateral ligaments was not negatively affected by TKR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…Given the caudal slope of the canine stifle, as compared with the relatively flat tibial plateau in people, it is likely that the canine stifle is more tolerant of small errors in component angulation in the sagittal plane. This is supported by results from a recent study by Baker et al in which the authors reported that joint kinematics and medial collateral ligament strains were similar in tibial components implanted at 8° and at the recommended 6° . In contrast, our data on the effects of frontal plane malalignment confirm that stifle loading is sensitive to errors in this plane .…”
Section: Discussionsupporting
confidence: 90%
“…Given the caudal slope of the canine stifle, as compared with the relatively flat tibial plateau in people, it is likely that the canine stifle is more tolerant of small errors in component angulation in the sagittal plane. This is supported by results from a recent study by Baker et al in which the authors reported that joint kinematics and medial collateral ligament strains were similar in tibial components implanted at 8° and at the recommended 6° . In contrast, our data on the effects of frontal plane malalignment confirm that stifle loading is sensitive to errors in this plane .…”
Section: Discussionsupporting
confidence: 90%
“…These changes alter loading within the joint and contribute to a negative mechanical environment of the TKR prosthesis, leading to the progression of disease and ultimately failure (21). As stated previously, kinematics of the canine stifle in a modified Oxford simulator to evaluate effects of variable implant placement has been reported (16).…”
Section: Introductionmentioning
confidence: 91%
“…A modified OKR described by Baker and colleagues was used to move a cadaveric limb through a range of passive motion allowing the kinematics of the stifle to be evaluated (16). Briefly, a hemipelvis specimen was bolted to a custom made bar of angle iron through the ischial tuberosity and sacroiliac joint of the ilium and the angle iron (▶ Figure 1) was attached to a mechanical crosshead.…”
Section: Test Apparatusmentioning
confidence: 99%
See 2 more Smart Citations